The Promessi sposi on Instagram: a teaching proposal in upper secondary schools - Maura Catania (Italiano a scuola)
This paper presents an educational proposal based on the reading of the Promessi sposi in a second-year upper secondary school class. Students were encouraged to rewrite selected passages from the novel in the form of Instagram posts. The use of Instagram supported the reworking and appropriation of the literary text in an activity that proved to be both engaging and motivating. It enabled students not only to share their creative outputs, but also to focus on aspects of the writing process that are sometimes overlooked. The activity also offered a valuable opportunity for metalinguistic reflection, allowing students to deepen their understanding of the Italian language in its various forms.